2017
DOI: 10.1111/xen.12339
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycolylneuraminic acid knockout reduces erythrocyte sequestration and thromboxane elaboration in an ex vivo pig‐to‐human xenoperfusion model

Abstract: The lack of Neu5Gc expression attenuated erythrocyte loss but did not prevent profound early onset thrombocytopenia or platelet activation, although TXB2 levels were decreased in the presence of Neu5GcKO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 37 publications
3
39
1
Order By: Relevance
“…Springer reported that NWNHPs do not express Neu5Gc antigens . Ex vivo pig organ perfusion models with human blood have been used to investigate the effect of anti‐Neu5Gc antibodies . However, the significance of expression of Neu5Gc in pigs has not been studied in vivo, as all OWNHPs express Neu5Gc.…”
Section: Discussionmentioning
confidence: 99%
“…Springer reported that NWNHPs do not express Neu5Gc antigens . Ex vivo pig organ perfusion models with human blood have been used to investigate the effect of anti‐Neu5Gc antibodies . However, the significance of expression of Neu5Gc in pigs has not been studied in vivo, as all OWNHPs express Neu5Gc.…”
Section: Discussionmentioning
confidence: 99%
“…This disproportionate rise in AST compared to ALT has been noted before 14 . The reason for this is unknown but could be due in part to elevated levels of hemolysis in the 2-gene and 3-gene groups 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes responsible for other xenoantigens, such as CMAH (cytidine monophosphate-N-acetylneuraminic acid hydroxylase critical for Neu5Gc biosynthesis) and B4GALNT2 (beta 1,4 N-acetylgalactosaminyltran sferase), have been identified as sources of porcine-specific epitopes bound by antibodies found in human serum. In each case, the deletion of the gene responsible for creating the specific glycan leads to greatly decreased recognition of porcine cells by antibodies in human serum, and reduction in complement-mediated destruction [38,39].…”
Section: Gene Knockoutmentioning
confidence: 99%